Respuesta :
Answer:
Average rate of change [tex]=-2[/tex]
Step-by-step explanation:
First derivative of function represents rate of change.
[tex]\frac{d}{dx}hx=\frac{d}{dx}(-x^2+8x+24)\\\\=-2x+8\\[/tex]
Now find out rate of change at end points
[tex](\frac{dh}{dx})_{x=0}=-2\times 0+8=8\\\\\\(\frac{dh}{dx})_{x=9}=-2\times 9+8=-10[/tex]
average rate of changes =[tex]\frac{First\ derivative\ at\ last\ point\ -first\ derivative\ at\ initial\ point }{last\ point-initial\ point}[/tex]
[tex]=\frac{-10-8}{9-0}\\\\=\frac{-18}{9}\\\\=-2[/tex]
Answer: ordered pairs (-2,-5) and (6,35)
Step-by-step explanation: